Erratic and Sentimental Geography: the Images of Modern Italian Cinema and its Themes in the Narrative of Isaac Rosa and Agustín Fernández Mallo - Mendieta Rodríguez, Elios (Escritura e Imagen, 2025)
This article analyses the novel Feliz final (Isaac Rosa, 2018) and the story «Un recorrido por los monumentos de La aventura» (Agustín Fernández Mallo, 2011), since both are in a singular dialogue, both thematically and structurally, respectively, with two outstanding films of cinematographic modernity: Viaggio in Italia (Roberto Rossellini, 1954) and L’Avventura (Michelangelo Antonioni, 1960). Thus, we study the way in which the images and signs of identity of this cinematographic period are recovered and updated in their narratives by the two writers, and we study in depth the formal structure of the two literary works and how the motif of the journey and that of the ghost are presented in them. The works by Rosa and Fernández Mallo thus constitute a tribute to the history of the seventh art while at the same time offering a new layer of meaning, thus confirming the synergy of comparative studies of film and literature in the Spanish-speaking world.